Communication and remote sensing integrated LEO satellites:architecture, technologies and experiment - Mugen PENG; Shijie ZHANG; Hongtao XU; Mengfei ZHANG; Yaohua SUN; Ying CHENG (Dianxin kexue)
Low earth orbit (LEO) satellite system is one of the most important infrastructures to gather spatial information and break the broadband digital divide.The integration of communication and remote sensing is an effective way to solve the existing problems of system independence, satellite resource waste, and late response to emergency service requests.Firstly, the status of communication and remote sensing in LEO satellite systems were outlined, and then a communication and remote sensing integrated scheme and architecture were put forward to meet the integration requirements.In addition, a hardware composition and corresponding experiment based on this architecture was introduced.Finally, the relevant challenges and future development were discused.